A molecular docking and molecular dynamics simulation study on the interaction between cyanidin‐3‐O‐glucoside and major proteins in cow's milk. Issue 1 (21st November 2020) - Pan, Fei; Li, Jiaxing; Zhao, Lei; Tuersuntuoheti, Tuohetisayipu; Mehmood, Arshad; Zhou, Na; Hao, Shuai; Wang, Chengtao; Guo, Yangkai; Lin, Wenxuan
Abstract: The objective of this study was to investigate the molecular interaction and complex stability of four major cow's milk (CM) proteins (α‐LA, β‐LG, αs1 ‐CA, and β‐CA) with cyanidin ‐ 3 ‐O ‐glucoside (C3G) using computational methods. The results of molecular docking analysis revealed that hydrogen bond and hydrophobic interaction were the main binding forces to maintain the stability of the C3G‐CM protein complexes. Molecular dynamics simulation results showed that all complexes except for C3G‐αs1 ‐CA were found to reach equilibrium within 50 ns of simulation. αs1 ‐CA and β‐CA switched to a more compact conformation after binding with C3G. Additionally, the radius of gyration, number of hydrogen bond, radial distribution function, and interaction energy showed that β‐CA is the best C3G carrier protein among the four CM proteins. This study can provide valuable information for CM proteins to serve as C3G delivery carriers. Practical applications: Anthocyanins (ACNs) are flavonoid‐based pigments that play an important functional role in regulating human's health. Cow's milk (CM) proteins are the most representative protein‐based carriers that can improve the short‐term bioavailability and stability of ACNs. Thus, it is important to study the interactions between ACNs and CM proteins at the molecular level for the development of effective ACNs delivery carriers. Our study showed that caseins (αs1 ‐CA and β‐CA) had more hydrophobic and hydrogen‐bonding sites with cyanidin ‐ 3 ‐O ‐glucoside (C3G) than whey proteins using computational methods. Among the four CM proteins, β‐CA was the best C3G carrier protein showing the best interaction stability with C3G. Thus, it is helpful for us to screen effective ACNs carriers from multiple protein sources by computational methods. Abstract : Cow's milk proteins (α‐LA, β‐LG, αs1 ‐CA and β‐CA) are potential good nano‐carriers for cyanidin ‐ 3 ‐O ‐glucoside (C3G). Hydrogen bonds and hydrophobic interactions were the main forces for the binding of C3G and cow's milk proteins. β‐CA is the best C3G carrier protein among the four selected cow's milk proteins based on the results of molecular dynamics simulation.